Exploring the Dynamics of Multilingualism: A Review - Yadav, Aditya Kumar (Journal of Advanced Research in English & Education, 2024)
Multilingualism stands as a cornerstone of human communication, embodying the rich tapestry of linguistic diversity that characterises our global society. This review synthesises recent research and theoretical perspectives to explore the multifaceted dynamics of multilingualism. From its cognitive benefits to its social implications and educational perspectives, multilingualism shapes our experiences and interactions in profound ways. The advent of globalisation has further complicated language dynamics, giving rise to new forms of multilingualism and linguistic hybridity. Despite its myriad advantages, multilingualism also poses challenges, including linguistic inequalities and barriers to equitable education. By recognizing the inherent value of linguistic diversity and promoting linguistic justice, we can harness the transformative potential of multilingualism to foster intercultural understanding and create more inclusive societies.